ANALISIS PEMBELAJARAN PENGGUNAAN TUTURAN IMPERATIF DALAM BERBAHASA INDONESIA PADA PESERTA DIDIK - H. Andi Asnawi; A.Andriyani Asra; Khaerul Khaerul Mahfud; Jihad Talib; Asdar; Irfan (Jurnal Pendidikan Sang Surya, 2024)
This research is qualitative research with the object of study being the analysis of imperative speech in the language of Class VIII students at SMP Negeri 3 Bulukumba. This research was carried out with the aim of describing the analysis of imperative speech in the language of Class VIII students at SMP Negeri 3 Bulukumba. Data was obtained using observation, listening, recording and note-taking techniques. The data obtained was analyzed qualitatively. The results obtained by the Imperative are usually characterized by the use of the imperatives hurry up, never mind, go, get around, look after, find, use, cut, stop; The request imperative is characterized by the use of the words please, request, ask for help, hope, I hope, ask, try ki bede; The Permission Imperative is characterized by the use of let, permitted, permitted, please, allow; The imperative of invitation is characterized by the use of the words come or come; The command imperative is characterized by the use of the words please, try.